Voyage du Jeune Anacharsis en Grece : vers le milieu du quatrieme siecle avant lere vulgaire / par J.-J. Barthelemy - Barthelemy, J.-J. (Jean-Jacques) 1716-1795. (Chez Rolland, 2015)
ΠΟΡΦΥΡΙΑΔΑ, 2010-12